Botulinum Toxin for the Treatment of Raynaud’s Conditions of the Hand: Clinical Practice Updates and Future Directions - Patrick O’Donohoe; Jake McDonnell; Justin Wormald; Lylas Aljohmani; Kevin Cronin; Laura Durcan; Oran Kennedy; Roisin Dolan (Toxins)
Raynaud’s conditions of the hand, referred to commonly as Raynaud’s phenomenon, both primary and secondary, represents a spectrum of disorders affecting the digits, characterised by recurrent episodes of vasospasm that result in a triad of symptoms: pain, pallor, and cyanosis. Various therapies, ranging from conservative hand therapy techniques to surgical sympathectomy, have been explored with inconsistent results. Recently, the local administration of botulinum toxin type-A (BTX-A) has re-emerged as a treatment option for this condition. This review delves into the mechanistic pathways of BTX-A therapy, optimal dosing concentrations, administration techniques, and its safety profile. A critical analysis of published studies to date demonstrates varied clinical efficacy of BTX-A in Raynaud’s conditions based on patient-reported outcome measures and objective measures of outcomes assessment. Thus, in order to accurately assess the clinical effectiveness of BTX-A in future robust studies, this review emphasises the importance of streamlining patient selection to minimise heterogeneity in disease severity, optimising recruitment to ensure adequate statistical power, and establishing sensitive outcome measures to monitor response and discern treatment efficacy. Additionally, addressing concerns such as minimising antibody resistance, extending the duration of treatment effects on tissues, and exploring new modalities to assess hand perfusion will be focal points for future research and BTX-A drug development.